Synthesis of a Ruthenium Complex Based on 2, 6-Bis[1-(Pyridin-2-yl)-1H-Benzo[d]Imidazol-2-yl]Pyridine and Catalytic Oxidation of (1H-Benzo[d]-Imidazol-2-yl)Methanol to 1H-Benzo[d]Imidazole-2-Carbaldehyde with H2O2. (February 2017) - Liu, Shenggui; Pan, Rongkai; Su, Wenyi; Li, Guobi; Ni, Chunlin
2, 6-Bis[1-(pyridin-2-yl)-1H-benzo[d]-imidazol-2-yl]pyridine (bpbp), which has been synthesised by intramolecular thermocyclisation of N 2, N 6 -bis[2-(pyridin-2-ylamino)phenyl]pyridine-2, 6-dicarboxamide, reacts with sodium pyridine-2, 6-dicarboxylate (pydic) and RuCl3 to give [Ru(bpbp)(pydic)] which can catalyse the oxidation of (1H-benzo[d]imidazol-2-yl)methanol to 1H-benzo[d]imidazole-2-carbaldehyde by H2 O2 . The optimal reaction conditions were: molar ratios of catalyst to substrate to H2 O2 set at 1: 1000: 3000; reaction temperature 50 °C; reaction time 5 h. The yield of (1H-benzo[d]imidazol-2-yl) methanol was 70%.